Women in China's long twentieth century - Hershatter, Gail.; University of California, Berkeley. Global, Area, and International Archive (Berkeley : Global, Area, and International Archive : University of California Press, 2007)
This guide for students of both Chinese and women's history synthesises recent research on women in 20th century China. It surveys over 650 scholarly works, exploring Chinese women in relation to marriage, family, sexuality, labour, and national modernity.
Introduction -- Marriage, family, sexuality, and gender difference -- Labor -- National modernity -- Afterthoughts.
Includes bibliographical references (pages 119-155) and index.
Print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Women -- China -- Social conditions -- 20th century; Women -- Employment -- China; Sex role -- China; Women and communism -- China; Feminism -- China; Marriage -- China -- History -- 20th century; Femmes -- Chine -- Conditions sociales -- 20e siècle.; Femmes -- Travail -- Chine; Rôle selon le sexe -- Chine; Femmes et communisme -- Chine; Féminisme -- Chine; Mariage -- Chine -- Histoire -- 20e siècle.; SOCIAL SCIENCE -- Women's Studies; HISTORY -- Asia -- General; Marriage; Feminism; Sex role; Women and communism; Women -- Employment; Women -- Social conditions; China; 1900-1999; History